2016
DOI: 10.1016/j.chom.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Zika Virus Pathogenesis

Abstract: SUMMARY Due to the ongoing Zika virus (ZIKV) epidemic and unexpected clinical outcomes including Guillain-Barré syndrome and birth defects, there is an urgent need for animal model development. We evaluated infection and pathogenesis with contemporary and historical ZIKV strains in immunocompetent mice and transgenic mice lacking components of the innate antiviral response. Whereas 4 to 6 week-old wild-type, Irf3−/−, Irf5−/−, and Mavs−/−, mice showed no overt clinical illness, Irf3−/− Irf5−/− Irf7−/− TKO and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

81
970
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 835 publications
(1,062 citation statements)
references
References 67 publications
81
970
0
11
Order By: Relevance
“…Thus, mouse models of ZIKV infection necessitate use of genetic deficiencies in IFNAR or antibody blockade of IFNAR 810 . To examine immune responses that control ZIKV neuropathogenesis, we first probed the cellular compartment responsible for the type I IFN-dependent block of ZIKV infection using irradiation-induced bone marrow chimeric mice between ZIKV-resistant C57BL/6 CD45.1 (WT) and ZIKV-susceptible interferon α/β receptor-deficient ( Ifnar1 −/− ) mice.…”
mentioning
confidence: 99%
“…Thus, mouse models of ZIKV infection necessitate use of genetic deficiencies in IFNAR or antibody blockade of IFNAR 810 . To examine immune responses that control ZIKV neuropathogenesis, we first probed the cellular compartment responsible for the type I IFN-dependent block of ZIKV infection using irradiation-induced bone marrow chimeric mice between ZIKV-resistant C57BL/6 CD45.1 (WT) and ZIKV-susceptible interferon α/β receptor-deficient ( Ifnar1 −/− ) mice.…”
mentioning
confidence: 99%
“…Now Zika virus (ZIKV) enters the stage. Prompted by previous studies in mice, in which the highest ZIKV load was found in the testes 3 , the detection of ZIKV in semen, and data that show male-to-female as each Sertoli cell sustains dozens of germ cells at different stages of their development.…”
mentioning
confidence: 98%
“…Prior to the work of Miner and colleagues 3,4 , another team of investigators reported that although ZIKV is able to replicate in a log-fold manner in immortalized human trophoblast cells lines, replication was not as robust in primary human trophoblasts isolated from healthy, term placental donors compared Earlier this year, the Washington University team developed a mouse model of ZIKV infection and demonstrated that peripheral visceral replication of ZIKV is inhibited by the type I interferon response 4 . In mice lacking the IFN α/β receptor 1 (Ifnar1 −/− ), ZIKV infection in adult, non-pregnant mice was associated with neurological destruction, accompanied by high levels of the virus in the brain and spinal cord, as well as in the spleen, testes and serum.…”
mentioning
confidence: 99%